2019
DOI: 10.11606/s1518-8787.2019053001303
|View full text |Cite
|
Sign up to set email alerts
|

Group prenatal care: effectiveness and challenges to implementation

Abstract: Group prenatal care is an alternative model of care during pregnancy, replacing standard individual prenatal care. The model has shown maternal benefits and has been implemented in different contexts. We conducted a narrative review of the literature in relation to its effectiveness, using databases such as PubMed, EBSCO, Science Direct, Wiley Online and Springer for the period 2002 to 2018. In addition, we discussed the challenges and solutions of its implementation based on our experience in Mexico. Group pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
0
11
3
5
Order By: Relevance
“…The evidence for improvements in knowledge of healthy behaviors was inconclusive: while knowledge of danger signs tripled among GANC participants, no statistical difference was found in knowledge of positive health behaviors between baseline and endline. This contradicts what is generally found in the literature [17,23,34,35], which has reported improvements in all aspects of knowledge. A recent study in Nepal [31] also found that knowledge of danger signs signi cantly improved, but knowledge of birth preparation decreased, from baseline to endline.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The evidence for improvements in knowledge of healthy behaviors was inconclusive: while knowledge of danger signs tripled among GANC participants, no statistical difference was found in knowledge of positive health behaviors between baseline and endline. This contradicts what is generally found in the literature [17,23,34,35], which has reported improvements in all aspects of knowledge. A recent study in Nepal [31] also found that knowledge of danger signs signi cantly improved, but knowledge of birth preparation decreased, from baseline to endline.…”
Section: Discussioncontrasting
confidence: 95%
“…We found few studies describing implementation experience; one study in India [15] reported similar challenges, including inadequate sta ng, issues with scheduling, and long wait times. One systematic review [35] also underscored demand-and supply-related challenges, including those related to personnel, participant retention, and physical resources, that occurred as part of GANC implementation.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for improvements in knowledge was inconclusive: while knowledge of danger signs tripled among GANC participants, no statistical difference was found in knowledge of positive health behaviors between baseline and endline. This contradicts what is generally found in the literature (17,21,36,37), which has reported improvements in all aspects of knowledge. A recent study in Nepal (38) also found that knowledge of danger signs improved, but knowledge of birth preparation decreased, from baseline to endline.…”
Section: Discussioncontrasting
confidence: 85%
“…The G-ANC model is being implemented and has been reported in more than 22 countries including India, but there are some challenges. Problems include additional resource allocation in terms of logistical support, as well as organizational issues, privacy concerns, and adaptation of materials for beneficiaries [ 4 ].…”
Section: Challenges To Providing Group Antenatal Care In Low- and Midmentioning
confidence: 99%